Study of ultrasonic vibration–assisted thread turning of Inconel 718 superalloy. (October 2019) - He, Yu; Zhou, Zhongming; Zou, Ping; Gao, Xiaogang; Ehmann, Kornel F
With excellent properties, high-temperature superalloys have become the main application materials for aircraft engines, gas turbines, and many other devices. However, superalloys are typically difficult to machine, especially for the thread cutting. In this article, an ultrasonic vibration–assisted turning system is proposed for thread cutting operations in superalloys. A theoretical analysis of ultrasonic vibration–assisted thread cutting is carried out. An ultrasonic vibration–assisted system was integrated into a standard lathe to demonstrate thread turning in Inconel 718 superalloy. The influence of ultrasonic vibration–assisted machining on workpiece surface quality, chip shape, and tool wear was analyzed. The relationship between machining parameters and ultrasonic vibration–assisted processing performance was also explored. By analyzing the motion relationship between tool path and workpiece surface, the reasons for improved workpiece surface quality by ultrasonic vibration–assisted machining were explained.